Pengaruh Kompetensi Coder terhadap Keakuratan dan Ketepatan Pengkodean Menggunakan ICD 10 di Rumah Sakit X Pekanbaru Tahun 2016 - Maimun, Nur; Natassa, Jihan; Trisna, Wen Via; Supriatin, Yeye (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
The accuracy in administering the diagnosis code was the important matter for medical recorder, quality of data was the most important thing for health information management of medical recorder. This study aims to know the coder competency for accuracy and precision of using ICD 10 at X Hospital in Pekanbaru. This study was a qualitative method with case study implementation from five informan. The result show that medical personnel (doctor) have never received a training about coding, doctors writing that hard and difficult to read, failure for making diagnoses code or procedures, doctor used an usual abbreviations that are not standard, theres still an officer who are not understand about the nomenclature and mastering anatomy phatology, facilities and infrastructure were supported for accuracy and precision of the existing code. The errors of coding always happen because there is a human error. The accuracy and precision in coding very influence against the cost of INA CBGs, medical and the committee did most of the work in the case of severity level III, while medical record had a role in monitoring or evaluation of coding implementation. If there are resumes that is not clearly case mix team check file needed medical record the result the diagnoses or coding for conformity. Keywords: coder competency, accuracy and precision of coding, ICD 10